Education Laboratory at PTN-BLU: A Review Study on Policy and Institutional Political Implications - Viktory N.J. Rotty; Ariel N. Rengkuan; Lando E. Sumarauw (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Educational laboratories at State Universities Public Service Agency (PTN-BLU) play a strategic role as academic nodes and institutional business units in supporting the tridharma of higher education. This study examines the dynamics of educational laboratory governance in the context of institutional politics and financial autonomy of PTN-BLU during 2015–2024. Using a qualitative descriptive approach and a literature study design, this study analysed policy documents, institutional reports, and accredited national publications. The main findings reveal four dominant patterns that hinder laboratory performance: internal policy discontinuity, inequality in resource allocation, political intervention in decision-making, and weak integration of digital systems. The fragmentation of SOPs and the dominance of bureaucracy worsen operational efficiency, while laboratories with higher commercial potential benefit from performance-based financing models. The study also shows that basic and social science laboratories are increasingly marginalized, widening the inequality gap. However, initiatives such as the digitization of laboratory management information systems, the establishment of multistakeholder advisory boards, asnd performance-based incentives showcase the potential for institutional reform. This research suggests the importance of adaptive internal policy design, fair budget distribution, and strengthening human resource capacity and digital accountability. Thus, the PTN-BLU laboratory can become a center of innovation and quality of education if it is carried out within an integrative and transformative governance framework.